Conflict Analysis in Mother-daughter Relationship in Okky Madasari's The Years of the Voiceless - Nisa Wiratie Wulantama; Nia Nafisah (Universitas Pendidikan Indonesia (UPI), 2022)
Conflict is an inevitable event that always occurs in human life as well in literary works. Okky Madasari’s The Years of the Voiceless shows conflicts that happen to a mother and a daughter who need to fight for women’s rights in the male-dominated world in the post-colonial era in Indonesia. They live based on their faiths and beliefs that are different due to the generational gap. By using the perspective of New Criticism, this study aims to investigate the sources of the conflict between them, how the conflicts are resolved, and how do the conflicts affect their relationship as mother-daughter. The result found that the conflicts that affect the mother-daughter relationship originate from external and internal conflicts. The conflicts are resolved through changes in the daughter’s character. This study proves that the generational gap, society, and characters’ personalities are the main causes of conflict in the mother-daughter relationships.